Development of Prototype model for Wireless based Controlled Pick and Place Robotic Vehicle - Low Kok Hau; Gowrishankar Kasilingam; K. Nithiyananthan (Institute of Advanced Engineering and Science, 2015)
The main aim of this research work is to develop and design a proto type model for a pick and place robotic vehicle with a soft catching gripper that can be controlled by android OS for remote operation. At the transmitting end using android application device, commands are sent to the receiver to control the movement of the robotic vehicle. Meanwhile at the receiving end four motors are interfaced to the microcontroller where two for them are used for arm movement while the other two are for the body movement. The android application device transmitter will acts as a remote control while the receiver end Bluetooth device is fed to the microcontroller to drive DC motors via motor driver IC for necessary work. Remote operation is achieved by any smart phone with AndroidOS; upon a GUI (Graphical User Interface) based touch screen operation. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7370